Odds Ratio of Increase in Hemoglobin Level Associated with Consumption of Songgak Coffee in Patients with Pulmonary TB - Lale Budi Kusuma Dewi; Sri Hartuti; I Wayan Getas; Agrijanti Agrijanti; Erlin Yustin Tatontos; Ida Bagus Rai Wiadnya; Siti Zaetun; Ari Khusuma (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Pulmonary TB cases in Indonesia are the second highest in the world. The incidence of Anemia in pulmonary TB patients can be as high as 90%. Anemia can lead to poor outcomes in the recovery of pulmonary TB. Songgak coffee is a coffee with a mixture of spices that is commonly consumed by the people of Central Lombok to make the body healthy and increase vitality, including pulmonary TB patients. Songgak coffee is made from 7 types of spices mixed with coffee. The results of previous research show that Songgak coffee has quite good antioxidant content and is an immunostimulant. Antioxidants may increase Hemoglobin levels. This was a case-control study. A total of 26 new pulmonary TB patients were divided into 2 groups. Group A received songgak coffee as an additional anti-TB drug, while group B received anti-TB drug therapy alone. Hemoglobin levels in groups A and B were measured before drug administration and 14 days after treatment. The data collected were nominal data, reported as increasing and non-increasing. A total of 12 out of 13 patients in group A had an increase in Hemoglobin, while only 1 person in group B had an increase in Hemoglobin. The odds ratio value for increasing Hemoglobin levels in pulmonary TB patients who consume songgak is 12. The odds ratio value for increasing Hemoglobin in pulmonary TB patients taking songgak is 12. The odds ratio value for increasing Hemoglobin levels in pulmonary TB patients who take Songgak is 12 times higher than in pulmonary TB patients who do not take Songgak.